Peningkatan Motivasi belajar IPA Menggunakan Pendekatan Saintifik pada siswa kelas IV SD IT AN-NUR - Nuradi, Farah Zhafiroh (Prosiding University Research Colloquium, 2021)
This study aims to increase motivation and science learning outcomes by applying a scientific model with the research subjects of fourth grade students at SD IT AN-NUR, Sawangan District, Magelang Regency. The research method used is CAR (classroom action research). The procedure in this study consisted of four stages, namely the planning stage, the implementation stage, the observation stage and the reflection stage. Data were taken through observation techniques, and questionnaires. The data were analyzed by means of descriptive qualitative and descriptive quantitative. In the first cycle got an average of 65.71. In the second cycle get an average of 79.04. Based on this, it can be concluded that the scientific model can increase learning motivation, thus the scientific model can be used as an alternative to problems regarding learning motivation.